Torsion of a spermatic cord cyst, a rare cause of acute scrotum on pre-pubertal children: About a case - S.P. Kebalo, MD; K. Doh, MD; T.B. Essobiyou, MD; K. Gnassingbe, MD (Elsevier, 2022)
Acute scrotum in children constitutes an emergency that can jeopardize both the functional and vital prognosis of the testicle. Among the various diseases presenting as acute scrotum, there are some very rare such as encysted hydrocele of the cord, which are difficult to suspect on clinical examination. We report a case of acute scrotum in a 09 year old child mistaken for a strangulated inguino-scrotal hernia after clinical examination, in whom intraoperative findings and anatomopathological examination led to the conclusion of encysted hydrocele of the cord torsion.